Nondestructive Evaluation of Far-Side Corrosion Around a Rivet in a Multilayer Structure. Issue 1 (2nd January 2018) - Kim, Jungmin; Le, Minhhuy; Lee, Jinyi; Kim, Sejin; Hwang, Young-Ha
ABSTRACT: This paper presents a sensor system for inspection of far-side defects around rivets in a multilayer structure. The sensor system includes 64 InSb Hall sensors arrayed in 0.52-mm intervals, over a total length of 33.28 mm. The sensor system was tested on two flat specimens, which have two layers of an aluminum alloy, with and without far-side defects around rivets. The sensor system performance was estimated via both the receiver operating characteristic and the probability of detection (POD) curves. Furthermore, a quantitative evaluation of the surface area, depth, and volume of a defect having a POD greater than 90% was carried out.